2013
DOI: 10.3389/fneur.2013.00122
|View full text |Cite
|
Sign up to set email alerts
|

Tau Clearance Mechanisms and Their Possible Role in the Pathogenesis of Alzheimer Disease

Abstract: One of the defining pathological features of Alzheimer disease (AD) is the intraneuronal accumulation of tau. The tau that forms these accumulations is altered both posttranslationally and conformationally, and there is now significant evidence that soluble forms of these modified tau species are the toxic entities rather than the insoluble neurofibrillary tangles. However there is still noteworthy debate concerning which specific pathological forms of tau are the contributors to neuronal dysfunction and death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 109 publications
(196 reference statements)
7
162
0
2
Order By: Relevance
“…In addition, there are other pathological brain proteins such as α-synuclein and tau protein which are also cleared by a number of enzymes and the processes are not efficient enough during old age. Thus the accumulation of the mentioned proteins is known to be the main causes of a number of chronic brain diseases [135].…”
Section: On Drainage During Sleepmentioning
confidence: 99%
“…In addition, there are other pathological brain proteins such as α-synuclein and tau protein which are also cleared by a number of enzymes and the processes are not efficient enough during old age. Thus the accumulation of the mentioned proteins is known to be the main causes of a number of chronic brain diseases [135].…”
Section: On Drainage During Sleepmentioning
confidence: 99%
“…T h e m e c h a n i s m l e a d i n g n o r m a l t a u t o b e c o m e hyperphosphorylated remains unknown and posttranslational modifications besides phosphorylation could regulate tau function and aggregation [58] , such as ubiquitination [59] , glycation [60] , glycosylation [61] , nitration [62] , polyamination [63] , proteolysis [64] , acetylation [58] , and methylation [65] .…”
Section: Other Post-translational Modifi Cationsmentioning
confidence: 99%
“…1). Mechanisms of clearance include proteolysis, autophagy, and proteasomal degradation [37,38]. In this context, it has been suggested that Aβ, tau, and α-syn toxic aggregates might be major therapeutic targets for these neurodegenerative disorders (Fig.…”
Section: Introductionmentioning
confidence: 99%